1993
DOI: 10.1172/jci116281
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in core nucleotide sequence of hepatitis B virus correlate with fulminant and severe hepatitis.

Abstract: Infection with hepatitis B virus leads to a wide spectrum of liver injury, including self-limited acute hepatitis, fulminant hepatitis, and chronic hepatitis with progression to cirrhosis or acute exacerbation to liver failure, as well as an asymptomatic chronic carrier state. Several studies have suggested that the hepatitis B core antigen could be an immunological target of cytotoxic T lymphocytes. To investigate the reason why the extreme immunological attack occurred in fulminant hepatitis and severe exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 37 publications
5
101
2
Order By: Relevance
“…The cytotoxic T-lymphocyte epitope in amino acid (aa) 18 to 27 was well-conserved, with mutations detected in only 2 of 15 patients. The greatest genomic variation was found in the central region of the core gene, as noted by Ehata et al 33 Patients exhibiting severe posttransplantation HBV recurrence exhibited significantly more precore/ core mutations and had a greater likelihood of being genotype D pretransplantation.…”
Section: Mutations In the Precore/core Regionmentioning
confidence: 68%
“…The cytotoxic T-lymphocyte epitope in amino acid (aa) 18 to 27 was well-conserved, with mutations detected in only 2 of 15 patients. The greatest genomic variation was found in the central region of the core gene, as noted by Ehata et al 33 Patients exhibiting severe posttransplantation HBV recurrence exhibited significantly more precore/ core mutations and had a greater likelihood of being genotype D pretransplantation.…”
Section: Mutations In the Precore/core Regionmentioning
confidence: 68%
“…Although HBeAg positivity in immunocompromised cancer patients appears to be a risk factor for HBV reactivation (Liang et al, 1990;Yeo et al, 2000b), this has not been found to be universally the case (Lok et al, 1991;Nokamura et al, 1996), and an increased risk may be partly attributed to the presence of the precore/core promoter HBV mutant (i.e. HBeAg negative/anti-HBe positive), which had been associated with severe fulminant hepatitis (Omata et al, 1991;Ehata et al, 1993;Liang et al, 1994;Nokamura et al, 1996;Steinberg et al, 2000;Yeo et al, 2000a, b). In addition, consistent with other reports, the baseline (pretreatment) liver function including ALT, total bilirubin and albumin levels did not appear to be associated with the development of HBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason why "mutation clustering regions" differed between type 1 and type 2 core sequences (Figs. 2, 3) and suggest the importance of minute alteration of the prototype sequence (11).…”
Section: Discussionmentioning
confidence: 99%